Fluorinated Azobenzenes for Shape‐Persistent Liquid Crystal Polymer Networks. (19th July 2016) - Iamsaard, Supitchaya; Anger, Emmanuel; Aßhoff, Sarah Jane; Depauw, Alexis; Fletcher, Stephen P.; Katsonis, Nathalie
Abstract: Liquid crystal polymer networks respond with an anisotropic deformation to a range of external stimuli. When doped with molecular photoswitches, these materials undergo complex shape modifications under illumination. As the deformations are reversed when irradiation stops, applications where the activated shape is required to have thermal stability have been precluded. Previous attempts to incorporate molecular switches into thermally stable photoisomers were unsuccessful at photogenerating macroscopic shapes that are retained over time. Herein, we show that to preserve photoactivated molecular deformation on the macroscopic scale, it is important not only to engineer the thermal stability of the photoswitch but also to adjust the cross‐linking density in the polymer network and to optimize the molecular orientations in the material. Our strategy resulted in materials containing fluorinated azobenzenes that retain their photochemical shape for more than eight days, which constitutes the first demonstration of long‐lived photomechanical deformation in liquid‐crystal polymer networks.